Resistencia a la corrosión de recubrimientos de CrN sobre sustratos de acero mediante EIE - Torres Luque, Magda Marcela; Ascolani, Hugo del Lujan; Olaya Florez, Jhon Jairo (Universidad Simón Bolívar, 2013)
Fil: Torres Luque, Magda Marcela. Universidad de los Andes; Colombia